A Controversy over the Expected Behavior of Deferred Tax Credits - Williams, John Joseph (Institutional Knowledge at Singapore Management University, 1977)
Presents commentaries on the article "The Expected Behavior of Deferred Tax Credits," by Hartwell C. Herring III and Fred A. Jacobs, published in the August 1976 issue of the periodical "Journal of Accountancy." Factors that contributed to the decrease in firms' credit account experience; Link between the deferred tax credit balance and the depreciation timing differences; Reaction of Herring and Jacobs to the criticisms.